ANALYSIS OF RISKS AND VULNERABILITIES OF COMPUTER SECURITY APPLYING ORIENTATED ARTIFICIAL INTELLIGENCE TECHNIQUES TO INSTITUTIONS OF HIGHER EDUCATION. - Castro-Maldonado, J.J.
Computer security has been presented as a primary instrument when safeguarding the most important asset in current organizations such as data and information, due to its value within proper knowledge management. In this sense, the institutions of higher education must responsibly handle the information of the actors that interrelate in it, such as students, teachers and administrative staff. The main objective of this article is to present a documentary research carried out to explore the deficiencies, risks and vulnerabilities in computer security that different organizations have, especially higher education institutions. This research work is framed within the epistemic current of positivism, applying the hypothetical-deductive method, with qualitative approach, aimed at developing an exploratory research work that proposes to address the situation on methods, techniques and strategies used for the identification of vulnerabilities and computer risks as a pillar cross-cutting scope of any organization, not only in the areas of technology but also in administrative areas. It was possible to show, thanks to the documentary analysis, that computer security must be taken into account in higher education institutions both to safeguard information concerning the operation of this, as to make your community aware of the proper handling of personal information that results in an adequate digital culture, and for this you can use different strategies, including artificial intelligence techniques to identify threats or characterize vulnerabilities.